Digital rectal examination (DRE) does not influence total serum levels of prostate specific antigen (tPSA), in individuals without prostate pathology - Figueirêdo,Maria de F. (2003)
OBJECTIVE: To evaluate if the digital rectal examination (DRE) performed before determination of total serum prostate specific antigen (tPSA) influences the levels of this protein. MATERIALS AND METHODS: Forty-eight men without a diagnosis of prostate pathology were assessed for tPSA levels, before and 30 minutes after DRE examination. Values of tPSA in the individuals' serum were measured by the electrochemoluminescence (ECLIA), in Roche's Elecys 1010 analyzer. RESULTS: DRE examination induced a modest elevation in tPSA values in 34 of the 48 men, with a variation in mean elevation from 2.19% in the age range ³ 70 years to 11.96% in the age range of 60-69 years. Additionally, moderate decreases in values were detected in 11 individuals and 3 did not present any alteration following the procedure. Differences in mean values of tPSA, pre- and post-DRE were not statistically significant, neither in the total sample of individuals or in the age range groups. CONCLUSION: DRE examination does not significantly influence the tPSA values in individuals under study.